CA IX Stabilizes Intracellular pH to Maintain Metabolic Reprogramming and Proliferation in Hypoxia - Benej, Martin; Svastova, Eliska; Banova, Radivojka; Kopacek, Juraj; Gibadulinova, Adriana; Kery, Martin; Arena, Simona; Scaloni, Andrea; Vitale, Monica; Zambrano, Nicola; Papandreou, Ioanna; Denko, Nicholas C.; et al. (Frontiers in Oncology, 2020)
Tumor hypoxia represents a severe microenvironmental stress that is frequently associated with acidosis. Cancer cells respond to these stresses with changes in gene expression that promote survival at least in part through pH regulation and metabolic reprogramming. Hypoxia-induced carbonic anhydrase IX (CA IX) plays a critical adaptive role in response to hypoxic and acidic environments by catalytically hydrating extracellular CO2 to produce bicarbonate and maintain optimal intracellular pH (pHi). We used proteome-wide profiling to study the cellular response to transient CA IX knockdown in hypoxia and found a decrease in the levels of key glycolytic enzymes and lactate dehydrogenase A (LDHA). Interestingly, the activity of LDH was also decreased when measured by native in-gel activity assay. These changes led to a significant reduction in glycolytic flux and extracellular lactate levels in cancer cells in vitro, contributing to a decrease in proliferation. Interestingly, addition of the alternative LDH substrate alpha-ketobutyrate restored LDHA activity, extracellular acidification, pHi and cellular proliferation. These results indicate that in the absence of CA IX, reduction of pHi disrupts LDHA activity and hinders the cellular capacity to regenerate NAD+ and secrete protons to the extracellular space. Hypoxia-induced CA IX therefore mediates adaptation to microenvironmental acidosis by two mechanisms, i.e. enzymatically by converting CO2 to extracellular bicarbonate, and indirectly by maintaining glycolysis-permissive intracellular milieu.